Outcomes of holmium laser enucleation of the prostate in men with a history of prostatitis: a retrospective study - Meera Bhanu Ganesh; Perry Xu; Nicholas Dean; Kyle Tsai; Jamie Michael; Alyssa McDonald; Devyn Taylor Coskey; Nabila Khondakar; Allaa Fadl-Alla; Amy Elizabeth Krambeck (Therapeutic Advances in Urology)
Background: Prostatitis can be challenging to treat. In refractory cases, prostatitis can be treated surgically with transurethral resection. Objectives: To examine the safety and efficacy of holmium laser enucleation of the prostate (HoLEP) as treatment in patients with prostatitis. Design and methods: Patients who underwent HoLEP at a single center between January 2021 and August 2023 were retrospectively reviewed. Preoperative, intraoperative, and postoperative parameters were collected and analyzed. Patients with an ICD-10 diagnosis of prostatitis were identified and contacted postoperatively to evaluate for recurrent symptoms. Statistical significance was defined as p  < 0.05. Results: We identified 918 patients, of whom 26 (2.8%) had a diagnosis of prostatitis. There were no differences in baseline characteristics between patients with and without prostatitis. Patients with prostatitis were less likely to have a history of a neurologic disorder ( p  = 0.035), less likely to be catheter-dependent ( p  = 0.005), and less likely to have a preoperative positive urine culture ( p  = 0.040). There were no significant differences in intraoperative and postoperative parameters between the two groups. There were 23/26 (88.5%) patients with follow-up. There were no episodes of recurrent prostatitis and one episode of UTI after surgery, with a mean follow-up of 19.39 months (range: 7.45–30.19, SD: 7.38). Conclusion: Prostatitis patients undergoing HoLEP had comparable safety and efficacy profiles to those who did not have prostatitis. On follow-up, 100% of patients with prostatitis did not experience recurrent prostatitis, suggesting that HoLEP may have a role in the management of prostatitis in the presence of benign prostatic enlargement.